The use of hyaluronic acid in a 3D biomimetic scaffold supports spheroid formation and the culture of cancer stem cells - Demirel, Gamze; Cakil, Yaprak Donmez; Koltuk, Gursel; Aktas, Ranan Gulhan; Caliskan, Mahmut (NATURE PORTFOLIO, 2024)
Three-dimensional (3D) bioprinting culture models capable of reproducing the pathological architecture of diseases are increasingly advancing. In this study, 3D scaffolds were created using extrusion-based bioprinting method with alginate, gelatin, and hyaluronic acid to investigate the effects of hyaluronic acid on the physical properties of the bioscaffold as well as on the formation of liver cancer spheroids. Conformational analysis, rheological characterization, and swelling-degradation tests were performed to characterize the scaffolds. After generating spheroids from hepatocellular carcinoma cells on the 3D scaffolds, cell viability and proliferation assays were performed. Flow cytometry and immunofluorescence microscopy were used into examine the expression of albumin, CD44, and E-cadherin to demonstrate functional capability and maturation levels of the spheroid-forming cells. The results show that hyaluronic acid in the scaffolds correlates with spheroid formation and provides high survival rates. It is also associated with an increase in CD44 expression and a decrease in E-cadherin, while there is no significant change in the albumin expression in the cells. Overall, the findings demonstrate that hyaluronic acid in a 3D hydrogel scaffold supports spheroid formation and may induce stemness. We present a promising 3D scaffold model for enhancing liver cancer spheroid formation and mimicking solid tumors. This model also has the potential for further studies to examine stem cell properties in 3D models.
Keywords: Hyaluronic acid; Stem cells; Spheroids; Three-dimensional cell culture; Biomaterials; CD44; Science & Technology - Other Topics